Pengaruh Investasi, Belanja Pemerintah dan Ekspor Produk Terhadap Pertumbuhan Ekonomi di Kota Medan - Aryabimo Reksapramudya; Hendra Harmain; Muhammad Lathief Ilhamy Nasution (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to determine the influence of investment on economic growth in the city of Medan, the influence of government spending on economic growth in the city of Medan, the influence of product exports on economic growth in the city of Medan and the influence of investment, government spending and product exports on economic growth in the city of Medan. The author's approach in this research is to use a quantitative and survey approach and the population in this research is the entire growth data for each variable starting from 2010-2022 using Non Probability Sampling with a total sampling method. The results of this research are that X1 (Investment) has a positive and significant effect on Y (Economic Growth), X2 (Government Spending) has a significant and positive effect on economic growth (Y), and X3 (product exports) has no effect on Y (Growth Economy). The variables investment, government spending and also product exports together or simultaneously and significantly influence variable Y (Economic Growth).